Mental Illness and Racial Disparities in Correctional Staff-Involved Violence: An Analysis of Jails in the United States - Semenza, Daniel C. (Journal of interpersonal violence, 2023)
In this study, we draw on theories of opportunity and focal concerns to examine how mental illness and race correspond to correctional staff-involved violence, particularly within the transient and diverse context of jails. Using a sample of 3,936 people incarcerated in jails from the 2011 to 2012 National Inmate Survey (NIS-3), we analyze how an individual’s mental health status (number of mental illness diagnoses) and race relates to the risk of staff-inflicted victimization. Using a series of Firth’s logistic regression models, we find that Black and Hispanic individuals are much more likely to be victims of correctional staff assault than their White counterparts. Those with one and two or more mental illness diagnoses are also at greater risk for staff-involved violence, respectively. Supplementary models show that those who suffer from serious mental illness are at particularly high risk for staff victimization. In a subsequent moderation analysis, we find that race does not condition the influence of mental health diagnoses on risk for staff-involved violence. Our findings reinforce the need for more research on correctional staff-involved violence and the implications of this research support calls for enhanced training of correctional staff regarding mental illness and racial bias.